New antimycobacterial agents in the pre-clinical phase or beyond: recent advances in patent literature (2001–2016) - da Silva, Patricia Bento [UNESP]; Campos, Débora Leite [UNESP]; Ribeiro, Camila Maríngolo [UNESP]; da Silva, Isabel Cristiane [UNESP]; Pavan, Fernando Rogério [UNESP] (Taylor & Francis, 2017)
Introduction: Tuberculosis, an infectious disease, has caused more deaths worldwide than any other single infectious disease, killing more than 1.5 million people each year; equating to 4,100 deaths a day. In the past 60 years, no new drugs have been added to the first line regimen, in spite of the fact that thousands of papers have been published on drugs against tuberculosis and hundreds of drugs have received patents as new potential products. Thus, there is undoubtedly an urgent need for the deployment of new effective drugs against tuberculosis. Areas covered: This review brings to the reader the opportunity to understand the chemical and biological characteristics of all patented anti-tuberculosis drugs in North America, Europe, Japan, and Russia. The 116 patents discussed here concern new molecules in the early or advanced phase of development in the last 16 years. Expert opinion: Of all 116 patents, only one developed drug, bedaquiline, is used, and then, only in specific cases. Another three drugs are in clinical studies. However, many other compounds, for which there are in vitro and in vivo studies, seem to fulfil the requisite criteria to be a new anti-tuberculosis agent. However, why are they not in use? Why were so many studies interrupted? Why is there no more news for many of these drugs?
Keywords: Drug patent; Mycobacterium tuberculosis; tuberculosis